Urine Color Analysis of Hydration Status in Employees Working in Bandung, Indonesia - Liza Karina Hauteas; Rudi Supriyadi; Yenni Zuhairini (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Dehydration can be compensated for by the body. However, if it occurs persistently, it can cause concentration problems, thermoregulation disorders, kidney damage, and other life-threatening disorders such as cardiovascular disorders. Urine color is a simple indicator to assess a person’s hydration status. The purpose of this study was to explore the hydration status of employees working in Bandung, Indonesia.Methods: This was a descriptive cross-sectional study conducted from March to November 2019. This study was a part of another study exploring urine color levels. Urine was collected on Sunday morning when the employees were free. Water intake and workload before urine examination were not taken into account. Hydration status was divided into three categories: well-hydrated, mild/moderate dehidration, and severe dehydration. A total sampling method was used to collect data.Results: In total, 178 subjects who met the study criteria participated in the study. The majority of respondents were 40-79 years old, male, did not have hypertension or diabetes, and active smokers. Most respondents experienced severe dehydration (44.7%) although 58.1% had consumed ≥8 glasses of water/day.Conclusion: More than half employees have consumed adequate amount of water; however, the majority are severely dehydrated when assessed based on their urine color. Further study on the balance of water intake and excretion is needed to explore the phenomenon of dehydration in the morning.